Classroom Application of Quantum Teaching in Elementary Science Learning: Penerapan Quantum Teaching dalam Pembelajaran IPA di Sekolah Dasar - Mica Amanda; Tri Wera Agrita; Aldino (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Science learning in elementary schools is crucial for building students’ conceptual knowledge and critical thinking. Specific Background: At SDN 201/VI Lubuk Napal, only 29% of fifth-grade students reached the minimum learning mastery in science and social science subjects. Traditional teacher-centered methods created low motivation and poor engagement. Knowledge Gap: Previous studies rarely examined Quantum Teaching specifically in the context of integrated science and social science learning at elementary level, particularly in rural schools. Aims: This study aimed to explore how the Quantum Teaching model supports classroom processes and outcomes in fifth-grade science learning. Results: Conducted as classroom action research in two cycles with 14 students, the findings showed clear progress. Teacher observation scores rose from 70.37% to 88.89%, while student observation increased from 66.67% to 88.89%. Learning mastery improved from 57.14% in the first cycle to 92.86% in the second cycle. Novelty: This research applied the TANDUR framework of Quantum Teaching in a real classroom with low motivation, demonstrating its practical relevance. Implications: The results highlight the potential of Quantum Teaching to create an interactive, enjoyable, and meaningful science learning environment that addresses both cognitive and participatory aspects. Highlight: Improved teacher and student participation during classroom activities. Higher mastery of science learning outcomes across two research cycles. Practical use of the TANDUR framework in a low-motivation classroom. Keywords: Quantum Teaching, Science Learning, Elementary Education, Classroom Research, Student Engagement